Development and maturation of cape gooseberry fruits - Diniz, Fábio Oliveira; Cardillo, Bruno Ewerton da Silveira; Novembre, Ana Dionisia da Luz Coelho (Comunicata Scientiae, 2025)
The cultivation of Physalis peruviana L. is an economic alternative, particularly for small farmers. However, there is a lack of available information on its cultivation under Brazilian edaphoclimatic conditions. Therefore, this study aims to evaluate the development and maturation of the fruits of P. peruviana according to the moment of flowering of the plant and the age of the fruit, in Piracicaba, São Paulo. A randomized block design with four replicates was used, and the treatments were arranged in a 2 × 4 factorial design, the first factor consisting of two moments of flowering of plants, 55 and 105 days after transplantation (DAT) and the second, represented by the age of the fruits, 45, 60, 75, and 90 days after anthesis (DAA). The physicochemical characteristics of 15 fruits from each repetition were evaluated immediately after harvesting. The necessary thermal accumulation from anthesis to the physiological maturity of the fruit is variable between the moments of flowering of the plant. Fruits harvested at 75 DAA, originating from the first moment of flowering (55 DAT), and at 60 DAA, originating from flowers issued at 105 DAT, present parameters (mass, size, color, and flavor) that characterize physiological maturity and have a quality standard that makes them suitable for marketing.